IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) MELALUI PEMANFAATAN BARANG BEKAS UNTUK MENGEMBANGKAN KREATIVITAS SISWA - Evita Liyana Sari; Fera Dwidarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to describe the use of the Pancasila Student Profile Strengthening Project (P5) programme in developing student creativity through the use of recycled materials. The method applied in this study is a descriptive qualitative approach with research subjects including students and teachers as classroom supervisors who are directly in the learning process. Data collection techniques in this study were conducted through observation and interviews. Meanwhile, data analysis techniques were carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of this study show that P5 plays a role in enhancing students' creativity, collaboration, and character. P5 also creates a supportive learning environment for students to channel their creative and innovative ideas. Additionally, P5 teaches students the importance of reusing used items and reducing waste. However, obstacles such as a lack of resources and inadequate time management were also identified.